1963
DOI: 10.1136/ard.22.3.153
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocalcinosis Articularis: Section II. Genetic Study

Abstract: Our first observations had shown that articular chondrocalcinosis (AC) occurred in several members of the same family. As the original material was 157 copyright.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1969
1969
1990
1990

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…veloping at a young age with rapid and progressive involvement of multiple joints and a second form developing at an advanced age (2,3) with progressive affliction of a few joints.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…veloping at a young age with rapid and progressive involvement of multiple joints and a second form developing at an advanced age (2,3) with progressive affliction of a few joints.…”
mentioning
confidence: 99%
“…However, in the group of patients studied by McCarty, no decline of synovial fluid Ca or alkaline phosphatase was found (9). Because of the growing evidence for an association of chondrocalcinosis with aging (1 3) diabetes (14), gout (1 5), postinfectious arthritis (16) hyperparathyroidism (17) and hemochromatosis (18,19), hypophosphatasia (20) as well as differences in clinical characteristics between familial (3,21) and idiopathic chondrocalcinosis, McCarty speculated that chondrocalcinosis and pseudogout represent a final common pathway for several separate metabolic disturbances (9). In line with this concept, it seemed worthwhile to characterize a group of patients from yet another geographic location in respect to measurements of PPi, Ca and alkaline phosphatase in synovial fluid of patients with pseudogout.…”
mentioning
confidence: 99%
“…It is postulated that either rapid cell division and matrix synthesis found in the base of ulcerating osteoarthritic cartilage or remodeling calcified sites are the source of the PPi in such osteoarthritic cartilage. It is further hypothlesized that this PPi output INTRODUCTION Clinical features of chondrocalcinosis during the last decade have attracted considerable attention (1)(2)(3)(4)(5)(6)(7)(8), but information concerning fundamental biochemical defects that would explain the deposition of the mineral phase, calcium pyrophosphate dihydrate (CaPPi) (9), found in articular cartilage, is meager. The major biochemical abnormality found so far has been a substantial synovial fluid-plasma inorganic pyrophosphate gradient (10)(11)(12); in one study red cell neutral Mg-dependent pyrophosReceived for puiblicationt 27 January 1975 antd int rovised form 23 Jutly 1975. phatase in a group of patients with chondrocalcinosis was not reduced below levels found in normal control subjects (13), and despite some contrary evidence (10,14,15), synovial fluid alkaline phosphatase levels have in most cases been within normal limits.…”
mentioning
confidence: 99%
“…Although menisectomy may accelerate degenerative changes and CPPD deposition,'5 16 Canada," Chile,6 Germany,' the United States of America,4 10 and Japan. 3 No further studies have been reported during the past six years.…”
Section: Discussionmentioning
confidence: 99%